Answer :

Let's break down the process of writing a recursive equation to model the given arithmetic sequence [tex]\( a_n = -4 + 1.5(n - 1) \)[/tex].

### Step 1: Identify the First Term
The first term in an arithmetic sequence, denoted [tex]\( a_1 \)[/tex], can be found by substituting [tex]\( n = 1 \)[/tex] into the given formula.

[tex]\[ a_1 = -4 + 1.5(1 - 1) \][/tex]

Calculate the expression inside the parentheses first:

[tex]\[ 1 - 1 = 0 \][/tex]

Then multiply by 1.5:

[tex]\[ 1.5 \times 0 = 0 \][/tex]

Thus,

[tex]\[ a_1 = -4 + 0 = -4 \][/tex]

So, the first term [tex]\( a_1 \)[/tex] is [tex]\(-4\)[/tex].

### Step 2: Identify the Common Difference
The common difference in an arithmetic sequence is the coefficient of [tex]\( n \)[/tex] in the term formula. From the sequence formula [tex]\( a_n = -4 + 1.5(n -1) \)[/tex], the coefficient of [tex]\( (n - 1) \)[/tex] is 1.5.

Thus, the common difference [tex]\( d \)[/tex] is 1.5.

### Step 3: Write the Recursive Equation
The general form of a recursive equation for an arithmetic sequence is:

[tex]\[ a_n = a_{n-1} + d \][/tex]

Here, [tex]\( a_{n-1} \)[/tex] represents the previous term, and [tex]\( d \)[/tex] is the common difference. Given our values:

- The first term [tex]\( a_1 = -4 \)[/tex]
- The common difference [tex]\( d = 1.5 \)[/tex]

The recursive equation is therefore:

[tex]\[ a_n = a_{n-1} + 1.5 \quad \text{with} \quad a_1 = -4 \][/tex]

This equation means that each term in the sequence is obtained by adding 1.5 to the previous term, starting from the first term which is [tex]\(-4\)[/tex].

### Summary
Chris can write the recursive equation to model the same arithmetic sequence as follows:

[tex]\[ a_1 = -4 \][/tex]
[tex]\[ a_n = a_{n-1} + 1.5 \quad \text{for} \quad n \geq 2 \][/tex]

This step-by-step breakdown allows us to convert the explicit formula [tex]\( a_n = -4 + 1.5(n - 1) \)[/tex] into a recursive equation suitable for modeling the same arithmetic sequence.